Géricault's Lion Devouring a Horse Stone Paper Matrix: Technical Study. Issue 2 (2nd April 2020) - Taylor, Christina; Rayner, Georgina; Wallace, Christopher; Eremin, Katherine
ABSTRACT: Théodore Géricault (1791–1824), one of the early proponents of lithography, experimented with the use of stone paper, a hand-coated paper that was formulated specifically for lithographic printing. Géricault's Lion Devouring a Horse stone paper matrix is in the collection of the Harvard Art Museums and is the focus of this study. X-ray fluorescence (XRF) analysis of the stone paper coating revealed the presence of lead and the absence of calcium, whereas previously published stone paper recipes all included calcium. Small samples were taken for analysis which confirmed that the material was dominated by lead white (basic lead carbonate) combined with a drying oil binder, casein and gum. Stone paper mockups revealed that the addition of casein was crucial to forming a resistant, stable coating for printing, but it also formed a brittle film, and casein was likely a contributing factor to the development of losses in the image during printing. Etch tests carried out on mockups showed that stone paper reacts more like a metal plate than a limestone, and that etching with tannic acid was most effective at stabilizing the matrix. Analysis of Géricault's stone paper in combination with the preparation of mockups revealed qualities of the process that help to understand the use and subsequent abandonment of the stone paper process.